The number of previous failed embryo transfer cycles is an independent factor affecting implantation rate in women undergoing IVF/ICSI treatment: A retrospective cohort study. Issue 9 (5th March 2021) - Wang, Yangyang; Tian, Yichao; Liu, Liu; Li, Tin-Chiu; Tong, Xiaomei; Zhu, Haiyan; Zhang, Songying
Abstract : Abstract: The implantation rate (IR) in assisted reproductive technologies such as in vitro fertilization (IVF) and intracytoplasmic sperm injection is affected by many different factors such as age, quality of embryo, and stage of embryo development. This study aimed to investigate to what extent the number of previous failed embryo transfer cycles is an independent factor affecting IR. This was a single-center, retrospective cohort study of a consecutive series of 6376 day-3 embryo transfer (ET) cycles following IVF between January 2012 and August 2018. None of the subjects underwent endometrial scratch/injury prior to the treatment cycle, or received intravenous immunoglobulin, steroid, dehydroepiandrosterone, intralipid or heparin during the treatment with the aim of improving implantation rates. Multiple regression analysis showed that the 3 most important independent factors affecting the IR, in decreasing of importance: age, frozen or fresh embryo transfer and the number of previous ET cycles. Having controlled for 2 of the more important confounding variables including maternal age and the type of embryo, the IR in women who had 0, 1, 2, and 3 or more previous failed ET cycles were 45.8%, 35.9%, 31.2%, 21.0%, respectively ( P  < .001). Repeated implantation failure is a significant independent factor affecting the IR. The number of previous failed ET cycles should be considered in counselling women regarding the prognosis of a further IVF-ET treatment cycle.